Case for geospatial border surveillance on the Bosnia-Herzegovina and Croatia border in response to the migrant crisis and hybrid warfare - Smailbegović, Amer (Array, 2020)
Bosnia-Herzegovina and Republic of Croatia share 931km of border (494km land and 425km riverine), which has been contentious for the greater part of the modern European history and represented one of the hardest and most-militarized border demarcating the frontiers of the major empires. Nowadays, it is in the process of becoming another hard-border between the Schengen-Zone EU and non-EU Western Balkans. In this study we are considering several strategic elements required for planning of effective and constructive border security, while countering variety of pseudo-hybrid warfare operations as well as tactical considerations when responding to crisis, communications and overall control of the fluid frontier. Strategic elements taken into consideration are: a) overall contiguity of the border, b) communications network / trafficability at border-crossing and c) geospatial support in the intelligence preparation of the area. Tactical elements considered are a) real-time geospatial support during operations b) alternative communications and vetting of alternative communications c) defensive operations (e.g. drone defense, jamming defense, incursion prevention). We are considering lessons-learned from the hostilities and frozen-conflicts in Yugoslavia, Ukraine, Afghanistan, Yemen and potential future conflagrations in Trans-Dnistria, Bosnia-Herzegovina, Kosovo* and the Baltics. We are using several criteria in understanding the required geospatial preparations required to undertake or defend against mass-migrations and potential hybrid threats such as unresolved territorial issues, population density information, infrastructure condition, land-use and overall completeness and availability of geospatial data.* Designation without prejudice to positions on status, and is in line with UNSCR 1244 and the ICJ Opinion on the Kosovo Declaration of Independence.